Advertisement Remove all ads

Simplify the Following Using the Formula: (A − B)(A + B) = A2 − B2: 113 × 87 - Mathematics

Answer in Brief

Simplify the following using the formula: (a − b)(a + b) = a2 − b2: 113 × 87

Advertisement Remove all ads

Solution

Here, we will use the identity  \[(a - b)(a + b) = a^2 - b^2\]

Let us consider the following product: \[113 \times 87\]

\[\because \frac{113 + 87}{2} = \frac{200}{2} = 100\] therefore, we will write the above product as:

\[113 \times 87\]

\[ = \left( 100 + 13 \right)\left( 100 - 13 \right)\]

\[ = \left( 100 \right)^2 - \left( 13 \right)^2 \]

\[ = 10000 - 169\]

\[ = 9831\]

Thus, the answer is 9831.

  Is there an error in this question or solution?
Advertisement Remove all ads

APPEARS IN

RD Sharma Class 8 Maths
Chapter 6 Algebraic Expressions and Identities
Exercise 6.6 | Q 4.5 | Page 43
Advertisement Remove all ads

Video TutorialsVIEW ALL [1]

Advertisement Remove all ads
Share
Notifications

View all notifications


      Forgot password?
View in app×